Smelting Industry in the Second Republic - Jarosz-Nojszewska, Anna (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
The article discusses the iron and steel industry of the Second Polish Republic. It starts with an assessment of the state of the sector at the beginning of independence, and the impact of incorporating parts of Silesia into the country, in particular in terms of available resources. While local coal was fit for processing into coke, special types of coal needed to be imported. The situation improved after the occupation of Zaolzie. Apart from prospecting works, the article explores investment processes in the sector, and the creation of conglomerates